2009
DOI: 10.1111/j.1399-6576.2009.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

The addition of fentanyl to 1.5 mg/ml ropivacaine has no advantage for paediatric epidural analgesia

Abstract: The addition of 0.2 mcg/kg/h fentanyl to 1.5 mg/ml ropivacaine increased the incidence of side effects without improvement of analgesia in infants and children undergoing hypospadias repair. The use of plain 1.25 mg/ml ropivacaine increased the need for rescue analgesia and this could be compensated by addition of fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Epidural analgesia was shown to provide good analgesia both intra-and postoperatively irrespective of the local anesthetic agent used: bupivacaine, levobupivacaine, or ropivacaine, there was an exclusion rate of 10% in one study (167) and patients having an abdominal incision were included in another (168). The addition of fentanyl to ropivacaine demonstrated increased analgesic efficacy for postoperative epidural infusions at low (0.125%) concentrations of ropivacaine (158).…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Epidural analgesia was shown to provide good analgesia both intra-and postoperatively irrespective of the local anesthetic agent used: bupivacaine, levobupivacaine, or ropivacaine, there was an exclusion rate of 10% in one study (167) and patients having an abdominal incision were included in another (168). The addition of fentanyl to ropivacaine demonstrated increased analgesic efficacy for postoperative epidural infusions at low (0.125%) concentrations of ropivacaine (158).…”
Section: Evidencementioning
confidence: 99%
“…A systematic review including trials in adults and children found that 'buffering' local anesthetics with sodium bicarbonate significantly reduces the pain of injection (88). Nitrous oxide has been shown to be effective in reducing pain, anxiety, and distress in cooperative children (157,158). See section 6.7 for information on the use of nitrous oxide.…”
Section: Evidencementioning
confidence: 99%